Sporadic medullary thyroid carcinoma: clinical features and diagnosis - Ziegler, Reinhard (Medullary thyroid carcinoma, 1992)
Medullary thyroid carcinoma (MTC) or C-cell carcinoma is a rather young endocrinopathy, i.e., its rareness in combination with its discrete clinical symptoms explains why it was only realized as a clinical entity about 30 years ago. Hazard et al. (1959) recognized the typical amyloid pattern and differentiated MTC from the melting pot of thyroid cancer. A few years later, calcitonin was discovered by Copp et al. (1962) and Hirsch et al. (1963) — however, some years passed before the ultimobranchial origin of calcitonin was demonstrated in 1967 (Bussolati and Pearse 1967). One year later it became evident that MTC exerts endocrine activity by secreting calcitonin in excessive amounts (Meyer and Abdel Bari 1968). Since then MTC has been handled as a specific disease quite different from the malignancies of the thyrocytes.